30‐day mortality following COVID‐19 and influenza hospitalization among US veterans aged 65 and older. Issue 9 (23rd May 2022) - Seligman, Benjamin; Charest, Brian; Ho, Yuk‐Lam; Gerlovin, Hanna; Ward, Rachel E.; Cho, Kelly; Driver, Jane A.; Gaziano, J. Michael; Gagnon, David R.; Orkaby, Ariela R.
Abstract: Background: COVID‐19 and influenza are important sources of morbidity and mortality among older adults. Understanding how outcomes differ for older adults hospitalized with either infection is important for improving care. We compared outcomes from infection with COVID‐19 and influenza among hospitalized older adults. Methods: We conducted a retrospective study of 30‐day mortality among veterans aged 65+ hospitalized with COVID‐19 from March 1, 2020–December 31, 2020 or with influenza A/B from September 1, 2017 to August 31, 2019 in Veterans Affairs Health Care System (VAHCS). COVID‐19 infection was determined by a positive PCR test and influenza by tests used in the VA system. Frailty was defined by the claims‐based Veterans Affairs Frailty Index (VA‐FI). Logistic regressions of mortality on frailty, age, and infection were adjusted for multiple confounders. Results: A total of 15, 474 veterans were admitted with COVID‐19 and 7867 with influenza. Mean (SD) ages were 76.1 (7.8) and 75.8 (8.3) years, 97.7% and 97.4% were male, and 66.9% and 76.4% were white in the COVID‐19 and influenza cohorts respectively. Crude 30‐day mortality (95% CI) was 18.9% (18.3%–19.5%) for COVID‐19 and 4.3% (3.8%–4.7%) for influenza. Combining cohorts, the odds ratio for 30‐day mortality from COVID‐19 (versus influenza) was 6.61 (5.74–7.65). There was a statistically significant interaction between infection with COVID‐19 and frailty, but there was no significant interaction between COVID‐19 and age. Separating cohorts, greater 30‐day mortality was significantly associated with older age ( p : COVID‐19: <0.001, Influenza: <0.001) and for frail compared with robust individuals ( p for trend: COVID‐19: <0.001, Influenza: <0.001). Conclusion: Mortality from COVID‐19 exceeded that from influenza among hospitalized older adults. However, odds of mortality were higher at every level of frailty among those admitted with influenza compared to COVID‐19. Prevention will remain key to reducing mortality from viral illnesses among older adults.